100Identification of a latitude gradient in the prevalence of Primary Biliary Cholangitis in Australia. (2nd September 2021) - French, Janine; Simpson-Yap, Steve; Ng, Justin; Angus, Peter; van der Mei, Ingrid; Gow, Paul
Abstract: Background: Primary biliary cholangitis (PBC) is an autoimmune destructive condition of the gall bladder, with environmental factors like sun exposure implicated in its aetiology, similar to multiple sclerosis. PBC prevalence varies significantly and appears to have a positive latitudinal gradient. To determine whether there was a latitudinal gradient of PBC prevalence in Australia using two methods of prevalence estimation: private pathology anti-mitochondrial antibody (AMA) results, the primary diagnostic test for PBC, and ursodeoxycholic acid (UDCA) prescriptions, the sole pharmacological treatment for PBC. Methods: We investigated the latitudinal variation in PBC prevalence across the states and territories of Australia (latitudinal range 18.0° to 42.7°S) using pathology-based (private pathology AMA results search (three of the major private pathology companies in Australia which cover 77% of all private pathology testing) and PBC-specific prescription databases (prescriptions for UDCA). Results: Pathology-based PBC prevalence was significantly increased with latitude, such that the postcodes in the highest quintile of latitude (encompassing the south coastal areas of the Australian mainland and insular Tasmania (latitude range -37.75 to -42.72)) had 1.83-times higher frequencies than those in the lowest quintile (encompassing tropical and southern Queensland (latitude range -18.02 to -27.59). Analogous results were seen for state-based UDCA prescriptions, being 2.31-times higher in Tasmania than Queensland. Conclusions: We have found for the first time that the prevalence of PBC significantly varies with latitude in Australia. While the most immediate mediating factors underlying this association would be ultraviolet radiation and vitamin D levels, studies to substantiate this mechanism are needed. Key messages: In line with some other autoimmune conditions, PBC shows a significant positive latitudinal gradient, with nearly 2-times higher prevalence in the southernmost state than the northernmost.